Boosting family engagement: Using EdTech to spark early childhood curiosity - Lee Bih Ni; Connie Cassy Ompok; Jusiah Idang (RSIS International, 2025)
This research examines the ways in which educational technology (EdTech) boosts early childhood curiosity by encouraging active involvement from families. Employing a synthesis-sources approach, the study combines primary data, such as user engagement metrics and parent surveys, with quantitative evaluations of child learning results. Results indicate that EdTech tools, including interactive apps and digital storytelling platforms, foster curiosity by facilitating exploratory learning, immediate feedback, and tailored experiences. Moreover, digital communication channels and collaborative activities enhance family involvement, bolstering children's cognitive and social growth. This research highlights the capability of EdTech to revolutionize early education by connecting home and school learning settings.